A comprehensive review on modeling of pneumatic and flash drying. Issue 1 (2nd January 2018) - Banooni, Salem; Hajidavalloo, Ebrahim; Dorfeshan, Masoud
ABSTRACT: Pneumatic conveying drying (PCD) is a widely used process in the industries and is a combination of heat and mass transfer and pneumatic handling technology. Drying processes consume large amounts of energy and, therefore, reduction in operating cost will be extremely beneficial for the industry. Many studies have been conducted to model and optimize the pneumatic drying. This review article focuses on the different strategies used in the literature to model pneumatic drying processes. An analysis is provided for the different mathematical modeling and its components such as balance and complementary equations and modeling assumptions. Two-fluid theory, Eulerian granular, and the discrete element method are reviewed as well as gas–solid flow modeling methods. In addition, the numerical methods and the main studied parameters in the field of pneumatic drying are investigated. To this end, heat and mass transfer coefficients, gas and dispersed phase properties are reviewed.